KUALITAS SILAGE JAGUNG DI DATARAN RENDAH TROPIS PADA BERBAGAI UMUR PANEN UNTUK SAPI PERAH (Tropical lowland maize silage quality from different age of harvesting for dairy cattle) - Despal Despal; Putri Hidayah; Ahmad Darobin Lubis (Buletin Ilmu Makanan Ternak, 2017)
Age of harvesting determine the maize forage condition prior to ensilage which influence the quality of silage produced. Nowadays, maize silage increasingly popular among smallholder dairy farmer in tropical lowland area, however, their optimum age of harvesting to produce the best silage quality have not been intensively studied. This experiment was aimed at finding the best age of maize plant to produce the best quality silage for tropical lowland. Four treatments (age of maize at harvesting), namely 60 d (T1), 70 d (T2), 80 d (T3) and 90 d (T4) of harvesting have been tested in producing whole plant maize silage. The silage was made in 2 kg laboratory plastic bag silo capacity and ensiled for 5 weeks. Physical (color, odor, texture, moisture and spoilage), fermentative (WSC, pH, DM, dry matter degradation, VFA, PK, protein degradation, NH3 and fleigh number), utility characteristic (in vitro rumen fermentability and digestibility) characteristics have been observed. Completely randomized design were used in this experiment except for utility characteristics which used block randomized design. Physical characteristics were analyzed using descriptive statistics, while fermentative and utility characteristics were analyzed using ANOVA. Significant different among the treatments were tested using polynomial orthogonal to find the best age of plant to produce the best silage quality. The results showed that DM content of maize plant increased linearly with the ages, but CP content decreased cubically in opposite curve shape to WSC content. The best silage quality material with 30% DM were not reached even at 90 d of harvesting. However, its CP contents decreased sharply after 80 d. Physical characteristics of the silage showed that no different between the treatments except for percentage spoilage silage. The lowest spoilage percentage was achieved if the plant harvested at 68 d, while the highest spoilage percentage was at 75 d. No statistically significant different were found in fermentative characteristic of silage among the treatments. All fermentative characteristics showed the silage in very good qualities. The DM loses during ensiling were not significantly influenced by the plant ages, although there were a trend toward decreasing number of loses with increasing of maize age of harvesting. Protein loses during ensiling were not influenced by the maize age. Fleigh number of the silage significantly increased after day 80. Fermentability of protein reduced with the age, while organic fermentability remained the same. Dry matter and organic matter digestibility of the silage were the best at day 90. It is concluded that the best whole maize silage quality in tropical lowland were resulted from maize harvested at 90 d.Keywords: maize, silage, tropical lowland, dairy, age harvesting